Igreja Católica, ASSESOAR e regime militar no Brasil: resistência e luta pela terra no sudoeste do Paraná (1962-1978) - Abatti, Alexandro (2018)
The Southwest region’s historical construction from Parana State is full of resistance, struggles about land, mobilizations and various popular organizations that have emerged throughout its history. Besides, it is a region, which has the rural environment as its main income plus an expressive number of small rural properties. My aim on this study is to understand an organization created in the 1960s and has a huge influence upon the social movements’ organization and development that have arisen on this region – the called ASSESOAR from Francisco Beltrão. This organization, founded by the Missionaries of the Sacred Heart (MSH), which was formed by young farmers and freelancers, promoted debates and consolidated the renewal process of PASTORAL proposed by the Second Vatican Council (1962-1965). Besides these, it is an organization that stands out by its strong performance on its area of coverage and that awakens on the decades of 1970s and 1980s the looks of the State that was under the command of the military regime. Considering this, our proposal manifests itself from the perspective of interpreting how it was possible for a popular organization, in the corners of the nation, to resist the intense manifestations of repression by the Exception State’s military organs. Even under this climate of tension, it is possible to analyze how the organization had the ability to reinvent itself at all times in order to be able to carry out its work until the institution, with help of the Catholic Church, which decided to give new clothing to ASSESOAR. It was necessary to search for mechanisms that evidenced the participation of the Belgian Missionaries, the Catholic Church and ASSESOAR. These mechanisms, which are detailed on this text, allow an approach about collective actions, understanding the regional conditions, the imaginary, the identity of the small farmers and, above all, the institution. The research is focused on a little known regional history, but it incorporates the attempt to show how much Parana Southwest’s history is important because of its peculiarities in the process of reocupation and colonization.